High Catalytic Selectivity of Electron/Proton Dual‐Conductive Sulfonated Polyaniline Micropore Encased IrO2 Electrocatalyst by Screening Effect for Oxygen Evolution of Seawater Electrolysis - Yuhan Shen; Shengqiu Zhao; Fanglin Wu; Hao Zhang; Liyan Zhu; Mingjuan Wu; Tian Tian; Haolin Tang (Advanced Science)
Abstract Acidic seawater electrolysis offers significant advantages in high efficiency and sustainable hydrogen production. However, in situ electrolysis of acidic seawater remains a challenge. Herein, a stable and efficient catalyst (SPTTPAB/IrO2) is developed by coating iridium oxide (IrO2) with a microporous conjugated organic framework functionalized with sulfonate groups (‐SO3H) to tackle these challenges. The SPTTPAB/IrO2 presents a ‐SO3H concentration of 5.62 × 10−4 mol g−1 and micropore below 2 nm numbering 1.026 × 1016 g−1. Molecular dynamics simulations demonstrate that the conjugated organic framework blocked 98.62% of Cl− in seawater from reaching the catalyst. This structure combines electron conductivity from the organic framework and proton conductivity from ‐SO3H, weakens the Cl− adsorption, and suppresses metal‐chlorine coupling, thus enhancing the catalytic activity and selectivity. As a result, the overpotential for the oxygen evolution reaction (OER) is only 283 mV@10 mA cm−2, with a Tafel slope of 16.33 mV dec−1, which reduces 13.8% and 37.8% compared to commercial IrO2, respectively. Impressively, SPTTPAB/IrO2 exhibits outstanding seawater electrolysis performance, with a 35.3% improvement over IrO2 to 69 mA cm−2@1.9 V, while the degradation rate (0.018 mA h−1) is only 24.6% of IrO2. This study offers an innovative solution for designing high‐performance seawater electrolysis electrocatalysts.